Initiating Developments of Nursing Informatics Within a Caring Perspective for Philippine Nursing - John Francis Faustorilla (Journal of Health and Caring Sciences, 2020)
Nursing informatics, despite its rich evolution and dynamic nature remains an emerging field in the Philippines. With its inclusion as a critical content in the Bachelor of Science in Nursing Curriculum, Policies, and Standards in 2008, various interpretations and adaptations were made evident thereby influencing Philippine Nursing. Critical discussions, whether or not Nursing Informatics affect the focus of nursing with the integration of information and communication technologies into nursing service delivery systems continue to exist. It is imperative that better understanding of the contributions of Nursing Informatics on Philippine Nursing from a historical perspective and declaring its implications for Philippine Nursing Practice initiated within a Caring viewpoint are addressed and illuminated. This paper aims to provide a description of the initiation of Nursing Informatics in the hope of establishing its ontological and epistemological position while providing a clearer understanding of its historical developments and influences on Philippine Nursing initiated within a caring perspective in a highly technological world.